2022
DOI: 10.21037/qims-22-252
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet transformation can enhance computed tomography texture features: a multicenter radiomics study for grade assessment of COVID-19 pulmonary lesions

Abstract: Background: This study set out to develop a computed tomography (CT)-based wavelet transforming radiomics approach for grading pulmonary lesions caused by COVID-19 and to validate it using real-world data.Methods: This retrospective study analyzed 111 patients with 187 pulmonary lesions from 16 hospitals; all patients had confirmed COVID-19 and underwent non-contrast chest CT. Data were divided into a training cohort (72 patients with 127 lesions from nine hospitals) and an independent test cohort (39 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…In addition to building machine learning models, we also found that the texture features of the images contributes to the prediction of NCRT response by LARC, consistent with previous studies (26,28). Moreover, wavelet transformation may enhance the texture characteristics of the images, improving the model performance (42), which may give some hints that this task can be verified in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to building machine learning models, we also found that the texture features of the images contributes to the prediction of NCRT response by LARC, consistent with previous studies (26,28). Moreover, wavelet transformation may enhance the texture characteristics of the images, improving the model performance (42), which may give some hints that this task can be verified in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…Although many researchers have used classical radiomic features (i.e., FO, GLCM, GLRLM, GLSZM, and GLDM), many others have achieved increased predictive power by exploiting high-level features, computed from filtered images by means of wavelet transforms, LoG filters, and intensity transformation. In particular, the wavelet-derived features have demonstrated their predictive capability in several contexts [ 7 , 8 , 9 , 11 , 12 ]. Despite their widespread use in the literature, comparing the different wavelets kernels is difficult because of the few studies [ 14 , 15 ] focused on the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Wavelet-derived features showed strong predictive capabilities in several contexts: tumor-type prediction of early stage lung nodules in CT [ 7 ], neoadjuvant chemotherapy treatment prediction for breast cancer in MRI [ 8 ], low-dose rate radiotherapy treatment response prediction of gastric carcinoma in CT [ 9 ], liver cirrhosis detection [ 10 ], glioblastoma multiforme differentiation from brain metastases in MRI [ 11 ], and grading of COVID-19 pulmonary lesions in CT [ 12 ]. The wavelet-derived features are calculated on the image decompositions—four for 2D images (e.g., X-ray, mammography, ultrasound, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Wavelet transforms can decompose image signals by using low-and high-pass filters and may amplify the heterogeneity information of texture features in radiological imaging, which is similar to previous studies. Jiang et al reported that wavelet transformation can enhance CT texture features and may be used to effectively assess the grade of pulmonary lesions caused by COVID-19 (29). Regarding the best performance in discriminating an expansive from an infiltrative front in tumour growth, Granata et al reported that wavelet transformation had the best performance in identifying tumour recurrence (30).…”
Section: Discussionmentioning
confidence: 99%